Substantiation of the conditions of obtaining porous carbon materials from pyrolyzed wood wastes by chemical activation of H3PO4 - Kuzmin, Oleg; Shendrik, Tatiana; Zubkova, Valentyna (My University, 2017)
The purpose of this publication is to search for alternative materials – food industry wastes; valuation of it’s use in the production of porous carbon materials for use in water treatment systems.
Keywords: піроліз; пиролиз; pyrolysis; адсорбент; адсорбент; adsorbent; кафедра технології ресторанної і аюрведичної продукції